The Structure and Functions of Soviet Security in Lithuania (1941–1954) - Petravičiūtė, Inga (Genocidas ir rezistencija, 1997)
The topic of the article is the structure and functions of the state security organs of the Lithuanian SSR in 1941–1954. The state security organs of the Soviet Union followed a strict internal structure, with each unit carrying out pre–defined functions. The change in the functions of the units also reflected the topicality of the state’s internal policy.
Keywords: repression structures; repressions; armed resistance; period of Stalinism